Cyanobacterial dynamics in shallow Lake Apopka (Florida, U.S.A.) before and after the shift from a macrophyte‐dominated to a phytoplankton‐dominated state. (23rd April 2015) - Waters, Matthew N.; Schelske, Claire L.; Brenner, Mark
Summary Paleolimnological data were used to reconstruct the primary producer history of shallow, hyper‐eutrophic Lake Apopka, Florida, U.S.A. Lake Apopka changed from a macrophyte‐dominated state to a phytoplankton‐dominated state in 1947. It has remained phytoplankton‐dominated despite efforts to re‐establish clear‐water conditions and submersed aquatic plants. Photosynthetic pigments, organic matter and nutrients (C, N, P) were analysed in a 4.28‐m sediment core that spans the past c. 8000 years. Our objectives were to: (i) reconstruct the primary producer history of Lake Apopka throughout its c. 8000‐year existence, (ii) determine whether the cyanobacterial dominance established in 1947 in Lake Apopka is the only period of cyanobacterial dominance in the lake's history and (iii) relate changes in the cyanobacterial community to known human impacts and recent management efforts. Lake Apopka possessed a macrophyte‐dominated primary producer community throughout most of its Holocene history, with diatoms, green algae and some cyanobacteria characterising the non‐macrophyte, primary producer component of the community. Since 1947, however, higher plants have been virtually absent in the lake and cyanobacteria have dominated the primary producer community, marking the first time that cyanobacteria have played such an important role in the lake. The cyanobacterial community itself has undergone multiple changes since 1947, confounding management efforts that have focused on a single driver of the primary producer community, that is phosphorus.